Establishment of an Efficient Immortalization Strategy Using HMEJ-Based bTERT Insertion for Bovine Cells - Zihan Zhang (MDPI AG, 2021)
Immortalized cell lines have been used in a wide range of applications in research on immune disorders and cellular metabolic regulation due to the stability and uniformity of their cellular characteristics. At present, the investigation into molecular functions and signaling pathways within bovine cells remains largely limited by the lack of immortalized model cells. Current methods for immortalizing bovine cells are mainly restricted to the ectopic expression of human telomerase reverse transcriptase (hTERT) through transient transfection or virus-mediated delivery, which have defects in efficiency and reliability. In this study, we identified bovine TERT (bTERT) as a novel potent biofactor for immortalizing bovine cells with great advantages over hTERT, and established an efficient and easily manipulated strategy for the immortalization of bovine primary cells. Through the homology-mediated end-joining-based insertion of bTERT at the ROSA26 locus, we successfully generated immortalized bovine fetal fibroblast cell lines with stable characteristics. The observed limitation of this strategy in immortalizing bovine bone marrow-derived macrophages was attributed to the post-translational modification of bTERT, causing inhibited nuclear localization and depressed activity of bTERT in this terminally differentiated cell. In summary, we constructed an innovative method to achieve the high-quality immortalization of bovine primary cells, thereby expanding the prospects for the future application of immortalized bovine model cell lines.